Evidence from complementation assays in vitro that U5 snRNP is required for both steps of mRNA splicing. - Winkelmann, G (1989)
We have established an in vitro complementation system that has allowed us to investigate the role of individual purified snRNPs in the splicing of pre-mRNA molecules. For the preparation of snRNP-depleted nuclear extracts we have first removed the majority of endogenous snRNPs from the nuclear extracts by one passage over an anti-m3G column and then degraded the remaining snRNPs with micrococcal nuclease. The mixture of snRNPs U1, U2, U4/U6 and U5, obtained by anti-m3G immuno-affinity chromatography, was functionally active and able to restore the splicing of snRNP-depleted nuclear extracts. Mono-Q chromatography was used for further fractionation of the snRNPs U1-U6. This produced three fractions that were highly enriched in snRNPs U1 and U2, U5 and U4/U6 respectively. Conditions were found where addition of the [U1, U2] and the U4/U6 snRNP fractions to the snRNP-depleted nuclear extracts gave rise to the formation of splice intermediates in the absence of any 3' cleavage/exon 1-exon 2 product formation. Only when purified 20S U5 snRNPs were added did both steps of the splicing reaction occur efficiently. Our data suggest that U5 snRNP is absolutely required for the second step of splicing and is needed further for efficient initiation of the splicing reaction. The requirement for U5 snRNPs for splicing was corroborated by glycerol gradient sedimentation analysis of the respective reconstituted pre-mRNP complexes. Stable and efficient formation of 50-60S spliceosomes was observed only in the presence of all snRNPs.